A Comparative Analysis of User Preference for Mobile Phones and Watches: A Study of Youth in and around Chandigarh - Suri, Gunmala (Gyan Management Journal, 2018)
With over a 210 million registered mobile phone users, India is one of the fastest growing mobile phone markets in India with almost 6.5 million users are being per month. According to TRAI statistics, almost 40% of India’s population will be mobile savvy by the end of 2010. Nokia dominates this market thanks to an early first mover advantage, with a presence in over 79000 retail outlets (both organized & unorganized).On the other hand, the Watch industry especially in the "wrist watch" category has reached the early stage of maturity in the product life cycle. The Indian watch market is estimated at 25 million units annually with 12 million falling in the organized sector, valued at approximately Rs 1,000 crore. Since 2001, there has been a 5% decline in the sales of wrist watches every year where as the mobile phones market has been on a considerable rise.With the proliferation of mobile phones in different consumer segments, a major challenge facing the watch industry is to identify and tackle the key drivers that are causing mobile phones to be looked at as substitutes for watches.The objective of this study lies in understanding the usage patterns for watches and cell phones among youth in the Chandigarh smart city. The study is done on a sample of200 young residents of Chandigarh and a self administered questionnaire is distributed and findings are sought.